The Hydrotropic Effect of Ionic Liquids in Water‐in‐Salt Electrolytes. Issue 25 (14th May 2021) - Becker, Maximilian; Rentsch, Daniel; Reber, David; Aribia, Abdessalem; Battaglia, Corsin; Kühnel, Ruben‐Simon
Abstract: Water‐in‐salt electrolytes have successfully expanded the electrochemical stability window of aqueous electrolytes beyond 2 V. Further improvements in stability can be achieved by partially substituting water with either classical organic solvents or ionic liquids. Here, we study ternary electrolytes composed of LiTFSI, water, and imidazolium ionic liquids. We find that the LiTFSI solubility strongly increases from 21 mol kg −1 in water to up to 60 mol kg −1 in the presence of ionic liquid. The solution structure is investigated with Raman and NMR spectroscopy and the enhanced LiTFSI solubility is found to originate from a hydrotropic effect of the ionic liquids. The increased reductive stability of the ternary electrolytes enables stable cycling of an aqueous lithium‐ion battery with an energy density of 150 Wh kg −1 on the active material level based on commercially relevant Li4 Ti5 O12 and LiNi0.8 Mn0.1 Co0.1 O2 electrode materials. Abstract : Ionic liquids boost the LiTFSI solubility in water from 21 to 60 mol kg −1 . Excess lithium salt solubility arises from a hydrotropic effect of the ionic liquids. This approach improves particularly the reductive stability of water‐in‐salt electrolytes, enabling stable cycling of commercially relevant LTO/NMC811 full cells.